Upaya Meningkatkan Kedisiplinan Belajar Pendidikan Agama Islam Melalui Pembiasaan di SDN 03 Pekan Labuah - Pronika, Nita (Indonesian Research Journal on Education, 2023)
There are several factors that cause a lack of student discipline when studying, namely; factors of students themselves who do not pay attention to the rules that apply in school, there are several factors of teachers who are less assertive in giving sanctions to students with problems and factors of parents who are less concerned about their children's education and their children are not accustomed to being disciplined at home partly because of their level of education and their respective activities. Therefore, efforts to improve their discipline is to provide advice-dvice and motivation about the importance of learning discipline to have, setting a good example for students, giving strict sanctions to students withproblems, and strengthening communication between parents and teachers about their attitudes and learning developments. How to apply this habituation method is done gradually, continuously and continues to evaluate student discipline so that it eventually becomes a habit. After the habituation method was carried out in an effort to improve student learning discipline, it was seen that their discipline was increasing and they have started to get used to being disciplined in doing the assignments given, entering class during study hours without orders from the homeroom teacher, not exercising during non-sports hours, and so on.